Futile or Fruitful? Institutional Conscience and Values Pluralism in Pediatric Care. - Weaver, Meaghann S.; Walter, Jennifer K. (American Journal of Bioethics, 2026)
The article focuses on the ethical challenges of institutional conscience claims in pediatric care, particularly regarding refusals of life-sustaining treatment for neurologically devastated children. It argues that rigid, rules-based institutional policies risk undermining respectful dialogue with families, especially those from minoritized or marginalized backgrounds, and may erode parental authority and relational autonomy—a concept emphasizing the interconnectedness of decision-making within family and care relationships. Through two pediatric case examples, the article advocates for time-limited trials, interdisciplinary review, and culturally sensitive, values-based discussions that acknowledge prognostic uncertainty and diverse conceptions of a "good life." It concludes that fostering mutual respect and pluralism in healthcare decisions better supports families and protects vulnerable pediatric patients than categorical institutional refusals grounded solely in institutional conscience.